2021
DOI: 10.3389/fimmu.2021.733539
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Immunogenomic Approach Identified SARS-CoV-2 Protective Immune Signatures in Asymptomatic Direct Contacts of COVID-19 Cases

Abstract: The response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is largely impacted by the level of virus exposure and status of the host immunity. The nature of protection shown by direct asymptomatic contacts of coronavirus disease 2019 (COVID-19)-positive patients is quite intriguing. In this study, we have characterized the antibody titer, SARS-CoV-2 surrogate virus neutralization, cytokine levels, single-cell T-cell receptor (TCR), and B-cell receptor (BCR) profiling in asymptomatic direct co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, more recent studies have started to address questions related to the transcriptional dynamics of viruses and infected cells upon infection 5 , 15 , 16 . SARS-CoV-2 is not an exception, and since the emergence of the COVID-19 pandemic, dozens of papers have been published addressing different aspects of the molecular biology of this virus 17 20 . Unfortunately, despite the large volume of available data, most scRNA-seq investigations on SARS-CoV-2 have focused mostly on characterizing cell tropisms or molecular mechanisms at macroscopic timepoints along the infection cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more recent studies have started to address questions related to the transcriptional dynamics of viruses and infected cells upon infection 5 , 15 , 16 . SARS-CoV-2 is not an exception, and since the emergence of the COVID-19 pandemic, dozens of papers have been published addressing different aspects of the molecular biology of this virus 17 20 . Unfortunately, despite the large volume of available data, most scRNA-seq investigations on SARS-CoV-2 have focused mostly on characterizing cell tropisms or molecular mechanisms at macroscopic timepoints along the infection cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, TRBV27 and TRAV12-3 have been frequently found to be upregulated in convalescent individuals 16,[43][44][45][46][47] Limitations of our study include the small sample size and the lack of internal controls, resulting in limited statistical power. To leverage additional data from the literature and put our own data in a broader context, we analyzed publicly available data sets of healthy vaccinees as well as of unvaccinated ASCT patients and their associated healthy transplant donors.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, few studies demonstrated overrepresentation or underrepresentation of particular V-, D- and J-segments in patients with different COVID-19 clinical picture ( 55 ). Asymptomatic patients had overrepresentation of TRAV (TRAV17, TRAV12-1, TRAV19, TRAV35, and TRAV41), TRBV (TRBV12-5 and TRBV19) ( 56 ), TRAJ16 and TRBJ2-1 ( 57 ) genes compared to patients with symptoms. Frequency of TRAV2, TRAJ8, TRAJ40, TRBV3-1 and TRBV5-1 were the highest in symptomatic patients ( 57 ) while four TCBV gene segments (TRBV5-6, TRBV14, TRBV13 and TRBV24-1) were found to be overrepresented in severe patients with little Jβ gene-segment skewing ( 58 ).…”
Section: Structure Of the T Cell Repertoire And Covid-19 Infectionmentioning
confidence: 99%